Meta-analyses on Corporate Social Responsibility (CSR): a literature review - Patrick Velte (Management Review Quarterly, 2021)
This paper addresses quantitative meta-analyses on corporate governance-related determinants and firms' (non) financial consequences of Corporate Social Responsibility (CSR). Legitimacy theory as our theoretical framework assumes that, through a social contract, a company must fulfil the respective society's values and expectations and gain legitimacy. We also rely on the business case argument, assuming a positive relationship between CSR and financial outcomes of the firm. This analysis focusses on 54 quantitative meta-analyses on CSR and includes a structured literature review in order to increase our knowledge, which corporate governance variables and proxies of firm's (non) financial outcome have been heavily included in archival research, and if there is an overall impact of these variables. Prior meta-analyses indicate that board independence, board gender diversity, and board size have a positive impact on CSR performance. Moreover, both CSR performance and environmental performance increase financial performance. This literature review makes a useful contribution to prior studies by summarizing the overall impact of corporate governance variables on CSR and their (non) financial consequences and by deducing recommendations for future research.
Keywords: G32; G41; M41; M42; M48; 650; Corporate Social Responsibility; Corporate governance; Legitimacy theory; Literature Review; Meta-analysis